Mechanism of criminal activity aimed at unlawful seizure of business entities’ assets - S. A. Tiulieniev (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of the investigative and judicial practice of investigation of criminal offences related to raiding, and also on the generalization of theoretical developments on the mechanism of criminal activity, the article proves that the mechanism of criminal activity of raiders is complex and multifaceted, since it is manifested in a variety of criminal offences which may sometimes even be embodied by criminal technologies. Based on the scientific research carried out, depending on the object and subject matter of the offence, it has been established that criminal offences related to raiding can be classified into several groups. In this regard, it is proposed that in the context of cognition of the criminal activity of raiders, the author distinguishes a specific mechanism of criminal activity, which should be understood as the internal systemic order of interaction of the forensically significant elements of criminal activity of a raider, a group of raiders and factors of objective reality, which is caused by the object and subject of criminal encroachment and is a reflection of criminal activity and is manifested in a group of constituent elements covering forensically significant information.